Cloud Point Behavior of Poly(trifluoroethyl methacrylate) in Supercritical CO2–Toluene Mixtures - James R. Zelaya; Gary C. Tepper (Molecules)
Supercritical CO2 (scCO2) is a versatile solvent for polymer processing; however, many partially fluorinated polymers exhibit limited solubility in neat scCO2. Organic cosolvents such as toluene can enhance polymer–solvent interactions, thereby improving solubility. The cloud point behavior of poly(2,2,2-trifluoroethyl methacrylate) (poly(TFEMA)) at 3 wt% concentration in scCO2–toluene binary mixtures was investigated over a temperature range of 31.5–50 °C and toluene contents of 0–20 wt%. Solvent mixture densities were estimated using the Altuin–Gadetskii–Haar–Gallagher–Kell (AG–HGK) equation of state for CO2 and the Tait equation for toluene. For all compositions, the cloud point pressure was observed to increase linearly with temperature. The cloud point pressure decreased monotonically with increasing toluene concentration and at the highest concentration of 20 wt% was reduced by approximately 40% in comparison to neat scCO2. The addition of toluene lowered the solvent density, but the increase in solvent–solute molecular interactions resulted in the observed decrease in cloud point pressure. Toluene is shown to be an effective cosolvent for dissolving poly(TFEMA) in scCO2, offering a promising approach to lowering operating pressures in fluoropolymer processing. Our results provide valuable phase behavior data for designing scCO2-based extraction, impregnation, and particle formation processes involving poly(TFEMA).